Theoretical analysis of solar thermal collector and flat plate bottom reflector with a gap between them - Hiroshi Tanaka (Energy Reports, 2015)
Augmentation of solar radiation absorbed on a flat plate solar thermal collector by a flat plate bottom reflector was numerically determined when there was a gap between the collector and reflector. The inclination of both the collector and reflector was assumed to be adjustable according to the season. A mirror-symmetric plane of the collector to the reflector was introduced, and a graphical model was proposed to calculate the amount of solar radiation reflected by the reflector and then absorbed on the collector. The performance was analyzed for three typical days at a latitude of 30êN. Solar radiation absorbed on the collector can be increased by the bottom reflector even if there is a gap between the collector and reflector. The optimum inclinations of both the collector and reflector are almost the same while the gap length is less than the lengths of the collector and reflector. However, the range of inclination of the reflector that can increase the solar radiation absorbed on the collector decreases with an increase in gap length, and the solar radiation absorbed on the collector rapidly decreased with an increase in the gap length when the reflector and/or collector were not set at a proper angle.
Keywords: 330